Disc cell therapy with bone-marrow-derived autologous mesenchymal stromal cells in a large porcine disc degeneration model - Omlor, Georg; Lorenz, S.; Nerlich, A. G.; Guehring, T.; Richter, Wiltrud (European spine journal, 2018)
Disc regeneration through matrix-assisted autologous mesenchymal stromal cell therapy seems promising against disc degeneration with convincing results in small animal models. Whether these positive results can be transferred to larger animal models or humans is unclear.
Gesehen am 24.03.2020